The Role of "Small Publics" in Teacher Dissent. Issue 1 (April 2016) - Stitzlein, Sarah M.; Rector‐Aranda, Amy
Abstract: In this essay, Sarah Stitzlein and Amy Rector‐Aranda, drawing on John Dewey's theoretical suggestions regarding how to best form publics capable of bringing about change through deliberation and action, offer teachers guidance on how to form and navigate spaces of political protest and become more effective advocates for school reform. Using Aaron Schutz's analysis of teacher activism as a point of departure, Stitzlein and Rector‐Aranda argue for the development in schools of "small publics, " that is, Deweyan democratic spaces within which teachers can dialogue and exchange ideas about the problems they face in the classroom. While Schutz treats this type of space merely as a stepping stone toward the real locus of political action, the power public, Stitzlein and Rector‐Aranda argue that small publics are themselves important spaces where teachers can work together to frame problems and build coalitions and solidarity with other groups in order to take action in the wider public sphere and bring about change in schools.